'n Narratologiese verkenning van die grufilm- en riller- subgenres - Ian Saunderson (Communicare)
This contribution was stimulated by a paper. ' Narrative In the news in the new South Africa • by David Wigston (UNISA). read at a seminar on aspects of popular culture held at RAU on May 311996. Wigston used the narrative model of Vladimir Propp to analyse the news content of Radio Moscow and Voice of America. Wigston did not arrive at final conclusions, and this contribution puts two popular film subgenres, the horror and the thriller. to the• test • of narrative theory.